Hubungan Sanitasi Tempat, Sanitasi Peralatan Dan Higiene Penjamah Dengan Bakteri Coliform Pada Depot Air Minum Di Kecamatan Sukmajaya - Librianti Virdha Amartya; Joko Tri; Dewanti Nikie Astorina Yunita (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
The increasing need for drinking water consumption has caused drinking water depots (DAM) to become one of the most popular choices among people. This is because the number of drinking water depots in Sukmajaya District has increased from 2019-2020 by 33%. To acquire consumption-safe status, DAM’s water must be free from coliforms. This study aims to determine the relationship between DAM’s sanitation hygiene with the number of Coliforms, with DAM in Sukmajaya District as the research subject. This study uses an analytical observational method using a cross-sectional approach. The research variables are place sanitation, equipment sanitation, and handler hygiene from the research population of 45 DAM units, with 31 DAM units taken as samples. By observation and interview with checklist sheets guided by the Minister of Health Regulation No. 43 of 2014, the results showed that among 31 DAMs, there were 15 (48.4%) DAMs that met the requirements for the total number of Coliforms, and 16 (51.6%) others did not meet the requirements for the total number of Coliforms. The results showed that there was a significant relationship between equipment sanitation (p = 0.001) and the hygienic conditions of the handlers (p = 0.001) in the presence of Coliform bacteria. Meanwhile, in the sanitation conditions (p=0.537) there was no significant relationship with the presence of Coliform bacteria. It can be concluded that there is a significant relationship between equipment sanitation and handler hygiene and the number of coliforms in DAM waters. Conversely, the place sanitation variable shows that there is no significant relationship with the number of Coliforms in DAM waters.